LEGAL PROTECTION FOR PREFERRED CREDITORS FOLLOWING THE CANCELLATION OF MORTGAGE RIGHTS BY COURT DECISION UNDER INDONESIAN LAW - Setiawan, Eddy; Suhardini, Eni Dasuki; Durahman, Dani (Universitas Labuhanbatu, 2025)
The holder of a Mortgage Right (Hak Tanggungan/HT) is granted the status of a preferred creditor under Article 1(1) of Law No. 4 of 1996 concerning Mortgage Rights (UUHT). HT is established through a Deed of Granting of Mortgage (APHT) and registered at the land office to obtain a Certificate of Mortgage Right (SHT). However, the enforcement of HT may be obstructed when third parties, particularly landowners, contest the object of HT in court, potentially resulting in cancellation decisions, as reflected in court rulings from Semarang, Cibinong, and Surakarta District Courts. This research aims to analyze the legal consequences and legal protection available to preferred creditors when HT is annulled by a court decision. The study employs normative legal research, which is grounded in the analysis of positive legal norms derived from statutory regulations (UUHT, KUHPerdata, HIR), reinforced by legal doctrines from scholarly literature, and jurisprudence from relevant court decisions. Utilizing a prescriptive analytical approach and secondary data sources, including legislation, books, journals, and verdicts, the findings show that HT cancellation leads to the reversion of land rights to third parties and alters the status of creditors from preferred to concurrent. Legal protection mechanisms available include filing a default lawsuit and submitting a request for asset seizure (conservatoir beslag) based on Article 1131 of the Indonesian Civil Code and Article 227(1) of HIR. Keywords: Cancellation ; Court; Decision; Liability; Rights